282 Follow-up for Evaluation for Nerve Repair Surgery: The Role of Socioeconomic and Geographic Factors in Victims of Violent Nerve Injury. (April 2022) - Liebendorfer, Adam; Marsh, Evan; Finnan, Michael; Bruce, Jordan; Skolnick, Gary; Kells, Amy
Abstract : OBJECTIVES/GOALS: We have created the first-ever database for all patients who have acute peripheral nerve injuries. Our goal is to use this data to construct two clinical scoring systems to facilitate triaging by emergency room physicians by 1.) identifying patients who would likely benefit from a nerve surgery, and 2.) identify patients who are less likely to follow up. METHODS/STUDY POPULATION: Based on 2, 606 consult emails from the Washington University in St. Louiss Division of Plastic and Reconstructive Surgery, from 2013 to 2019, we have identified more than 600 patient cases in which patients presented after an injury with any kind of nerve deficit. We have defined nerve deficits as any abnormality on motor or sensory exam of the extremities, excluding those younger than 18 years old and those with other disease processes that may affect function of the peripheral nervous system. Data for these patients was collected from electronic medical records and include handedness, nerve injured, operative details, area deprivation index decile, mechanism of injury, insurance and employment status, and whether injuries were a result of work or violence. RESULTS/ANTICIPATED RESULTS: Our plan is to provide the first descriptive statistics for such a population, as well as multiple regression analysis for our two endpoints, loss to follow up and need for surgery. Following regression analysis, we also look to perform cluster analysis to further study co-occurring clinical and social features that affect our endpoints. We are excitedly awaiting to perform the analysis after the final data has been collected. DISCUSSION/SIGNIFICANCE: Nerve injury is a common symptom of penetrating injuries. Many of the socioeconomic factors associated with increased risk for violent injury are also risk factors for decreased rates of follow up. This problem is particularly worrisome given that nerve repair surgery is only viable as an option to return function within the first year after injury.